Analisis Dampak Pengoperasian City Plaza Terhadap Karakteristik Lalu Lintas - Ida Farida; Dela Misela (Institut Teknologi Garut, 2026)
The Jl. Cimanuk-Jl. Guntur Interchange is a residential, shopping, and office area close to a new shopping center. However, traffic queues and delays cause congestion, mainly due to the large number of vehicles parking on the roadside, which reduces road capacity. This research uses a descriptive quantitative method that aims to analyze volumes, measure traffic performance and redesign traffic using PTV Vissim Student software. The results showed that the highest traffic volume reached 6550.8 skr/hour on May 26, 2024 between 17.00-18.00 WIB with a road capacity of 4293.156 skr/hour. Vehicle travel time was recorded at 15.69 seconds with a speed of 19.2 km/h for Jl. Cimanuk and 23.25 km/h for Jl. Guntur. Traffic performance at the Jl. Cimanuk-Jl. Guntur intersection is considered poor with a level of service of 31.76 sec/skr which is classified as poor (D), so improvements are needed in service at the intersection. In conclusion, to overcome the problem of unstable traffic at the Jl. Cimanuk-Jl. Guntur intersection, better management of vehicle flow is needed. Suggested measures include the installation of no-parking signs and additional parking attendants to discipline vehicles blocking the road.